2015
DOI: 10.1140/epjb/e2015-60286-y
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of simplified scattering from rough surfaces to reflection in fractional space

Abstract: In this paper, scattering of incident plane waves from rough surfaces have been modeled in a fractional space. It is shown how wave scattering from a rough surface, could be a simple reflection problem in a fractional space. In the integer space, fluctuations of the surface result in wave scattering while in the fractional space these fluctuations are compensated by the geometry of the space. In the fractional space, reflection leads to the same results as the scattering in the integer space. To make it more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…If K(τ ) ∝ δ(τ ) where δ(τ ) is Dirac delta function Eq. 1 will remain unchanged [18][19][20][21]. For a discrete dynamical procedure Eq.…”
Section: Non-markovian Boolean Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…If K(τ ) ∝ δ(τ ) where δ(τ ) is Dirac delta function Eq. 1 will remain unchanged [18][19][20][21]. For a discrete dynamical procedure Eq.…”
Section: Non-markovian Boolean Dynamicsmentioning
confidence: 99%
“…If K(τ ) = δ(τ ), where δ(τ ) is the Kronecker delta function, eq. ( 1) will remain unchanged [18][19][20][21]. Therefore eq.…”
mentioning
confidence: 99%
“…Since the publication of this seminal work by Berry, numerous studies have been published on related aspects of the problem, some of which can be found in Refs. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The overall majority of these studies are either purely numerical and/or the scattered intensity is not obtained in a closed form expression but rather more typically as an infinite series where the terms depend on the self-affine parameters.…”
Section: Introductionmentioning
confidence: 99%
“…An event in the far past is supposed to have less effect on the node's dynamics, when compared with the same event happening in a near past. As a result of this kernel, the governing equation for the node's dynamics is turned into a fractional [51][52][53][54][55][56] order BA-like equation.…”
Section: Introductionmentioning
confidence: 99%